RELIGIUSITAS MASYARAKAT BATAK TOBA DI ERA MODERN (STUDI KASUS DI KECAMATAN SIANJUR MULAMULA SAMOSIR) - Baringin, Desmon Baringin Sitompul (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
The Toba Batak people adhere to Christianity. Christianity for Toba Batak people does not completely eliminate their traditional belief in ancestral spirits and other gods. People also follow developments in technology and social media to promote their culture and religious traditions to the wider community. Christianity in this region does not completely replace the belief traditions that have existed for a long time. However, people combine these two beliefs in their daily lives. The method used in this study is a qualitative method, to understand the phenomena experienced by the research subjects holistically. The development of the religiosity of the indigenous Toba Batak community in Sianjur Mulamula shows that ancient beliefs have faded with the presence of modern religion today so prefer to adopt Christianity rather than practice ancient beliefs. However, there are still people who carry out ancient religious rituals in a closed way. The development of Christianity in Sianjur Mulamula is very rapid and is still influenced by the traditions that bind the original Toba Batak beliefs so are two views, namely, still believing in Christian beliefs and on the other hand, still believing in the Batak belief traditions.